A common law view of "carrying on a trade" - Mkonza, Qhinga Aidan (Rhodes University, Faculty of Commerce, Department of Accounting, 2018)
The term "trade" is defined in very wide terms in the Income Tax Act and includes a "business" and a "venture" . For a taxpayer to claim certain deductions in arriving at taxable income, the taxpayer must be carrying on a trade. The expression "carrying on a trade" is not defined in the Income Tax Act. Whether or not a taxpayer is carrying on a trade is a matter of fact. Case law has established certain principles and tests to be applied in determining whether a taxpayer is carrying on a trade. The goal of the thesis was to determine to what extent an activity can be considered as carrying on a trade. This research focused on the letting of property, money-lending, or farming operations in relation to carrying on a trade or business or engaging in a venture. The thesis also discussed at what stage a taxpayer ceases to carry on a trade and what the tax consequences are of ceasing to trade. An interpretative research approach was used in the research as it sought to understand and describe. No interviews conducted for this research and the data used for the research are publicly available. It was established that "carrying on a trade" , including a business, requires an active step taken by the taxpayer to trade. It involves regularity of buying and selling or rendering of services. The intention to trade is important but it is a subjective matter and cannot be persuasive in determining whether a taxpayer is carrying on a trade; objective factors are also considered. If the stated intention to trade matches the actions of the taxpayer, the taxpayer will be considered to be carrying on a trade. In determining whether a taxpayer is carrying on a trade each case must be considered with its own merits.
Keywords: Business; Common law -- South Africa; Income tax -- South Africa; Agriculture -- Taxation -- South Africa; Property tax -- South Africa; Moneylenders -- Taxation -- South Africa